2017
DOI: 10.17219/acem/41978
|View full text |Cite
|
Sign up to set email alerts
|

Insights into novel anticancer applications for apigenin

Abstract: Flavonoids, naturally occuring derivatives of 2-phenyl-benzo-γ-pyrone, are widespread in plants as coloring substances. Apigenin (4' ,5,7,-trihydroxyflavone (5,7-dihydroxy-2-(4-hydroxyphenyl)-4H-1-benzopyran-4-one), molecular formula C₁₅H₁₀O⁵, is a flavonoid present in many fruits and vegetables, primarily in citrus fruits, apples, parsley and celery leaves. It is also found in some medicinal plants, including chamomile flowers, thyme, oregano, peppermint, lemon balm and yarrow, as a 7-O-glycoside with anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Found plentifully in many medicinal plants and in many vegetables and fruits, apigenin, a naturally-occurring flavonoid, has several physiological functions [155,156]. It showed anticancer activity via JAK/STAT pathway inhibition by reducing phosphorylated JAK1/2 and STAT3 in breast cancer (BT-474) cells [25].…”
Section: Apigeninmentioning
confidence: 99%
“…Found plentifully in many medicinal plants and in many vegetables and fruits, apigenin, a naturally-occurring flavonoid, has several physiological functions [155,156]. It showed anticancer activity via JAK/STAT pathway inhibition by reducing phosphorylated JAK1/2 and STAT3 in breast cancer (BT-474) cells [25].…”
Section: Apigeninmentioning
confidence: 99%
“…Apigenin is a flavonoid abundantly available in Apium leaves. It reportedly has anti-cancer properties [reviewed by Kowalczyk et al (2017)] and can enhance skeletal muscle hypertrophy and myoblast differentiation in mice (Jang et al, 2017). As aforementioned, the enzyme responsible for conversion of naringenin to apigenin is known and its manipulation leads to an increased level of apigenin (Tan et al, 2017).…”
Section: Breeding For Nutraceuticals and Food Safetymentioning
confidence: 99%
“…Studies have shown that apigenin is a potent antioxidant, antiviral, antimicrobial and chemo preventive agent. [4][5][6][7] In the structure of this compound three hydroxyl groups together with double bonds at C2 and C3 are present. Such chemical structure provides that apigenin can acts as a phytoestrogen.…”
Section: Introductionmentioning
confidence: 98%